2009
DOI: 10.1002/qua.22267
|View full text |Cite
|
Sign up to set email alerts
|

Compound I in horseradish peroxidase enzyme: Magnetic state assessment by quadratric configuration interaction calculations

Abstract: Quadratic configuration interaction procedure with single and double electronic excitations (QCISD) has been used, for the first time, to calculate the electronic structure of the Compound I (CpdI), which represents a key intermediate in the catalytic cycle of Horseradish Peroxidase (HRP) enzyme. The QCISD method is applied to lowest quasi-isoenergetic doublet and quartet spin multiplicity and results compared with density functional theory (DFT/B3LYP) data. This investigation shows that, at present, QCISD is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…In particular, C c P Cpd I has a protein radical (on Trp 191 ), while HRP and APX have a heme-based radical. Extensive computational studies using density functional theory, quantum mechanics/molecular mechanics and molecular dynamics studies have been performed on the various stages of the catalytic cycle of peroxidases and particularly on Cpd I [ 44 , 45 , 46 , 47 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. These studies ( Scheme 1 ) confirmed Cpd I as a triradical species with three unpaired electrons, whereby two of those are on the metal (in the π* xz and π* yz orbitals), while the third radical is non-metal based [ 53 , 57 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, C c P Cpd I has a protein radical (on Trp 191 ), while HRP and APX have a heme-based radical. Extensive computational studies using density functional theory, quantum mechanics/molecular mechanics and molecular dynamics studies have been performed on the various stages of the catalytic cycle of peroxidases and particularly on Cpd I [ 44 , 45 , 46 , 47 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. These studies ( Scheme 1 ) confirmed Cpd I as a triradical species with three unpaired electrons, whereby two of those are on the metal (in the π* xz and π* yz orbitals), while the third radical is non-metal based [ 53 , 57 , 61 ].…”
Section: Introductionmentioning
confidence: 99%